ASWED: A Digital Learning Media to Improve Students’ Istima’ and Qira’ah Skills in Islamic Junior High Schools - Lionyza Zaneta Rasendria Kirana; Muhammad Ardy Zaini; Mokhammad Miftakhul Huda (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aimed to develop and evaluate ASWED (Arabic Story with Educaplay), a digital learning media designed to improve students’ Arabic listening (istima’) and reading (qira’ah) skills at the junior high school level. This study aims to examine: (1) the development process of the ASWED digital media for teaching istima’ and qira’ah; (2) its quality based on expert and user evaluations; and (3) its effectiveness in improving students’ istima’ and qira’ah skills. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, the media was developed through content design, integration of narration with Educaplay, and expert validation. Data were collected through validation sheets, pretest–posttest instruments, and interviews with teachers and learners. The results showed that ASWED was rated “very feasible” by experts with scores of 86.15% (material), 100% (media), and 85.3% (practitioners). In terms of effectiveness, the experimental group demonstrated a significant improvement from pretest to posttest (M = 63.77 → 77.79; p < .001, d = 0.56), while the control group experienced a significant decline (M = 84.23 → 44.73; p < .001, d = −2.41). Independent t-tests revealed a large effect size in favor of the experimental group (d = 2.34). Furthermore, student responses indicated that ASWED was engaging, motivating, and suitable for independent learning. These findings highlight that ASWED not only improves language competence but also addresses challenges in conventional Arabic instruction by integrating digital innovation. Future research may extend this approach to other Arabic skills and broader educational contexts.